PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN PADA FOOD CENTER (UKM BINAAN PJT I) DI KAWASAN WISATA WADUK SELOREJO MALANG - Jovita Vicka Bayu Wardhani; Dewi Ratih (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
The tight competition in the business world requires anorganization to create a marketing mix strategy to market theproducts sold and increase sales turnover. This research analyzesthe influence of marketing mix which includes product, price, place,promotion, people, physical evidence and process to purchasedecision.This research is a quantitative research. Case study was conductedat the food center in the tourist area of Selorejo Dam Reservoir.Data obtained from 80 respondents through direct observation(observation) and questionnaires on people who have / have visitedSelorejo Reservoir and made purchases of products in the foodcenter Selorejo Reservoir Malang. Method of data analysis usingquantitative analysis that is doubled linear regression.The analysis performed shows the following results: 1) Product,price, promotion, place, person, physical environment and processsimultaneously / together positively influence purchasing decision,2) Product, promotion, place, person and process partially have Apositive influence on purchasing decisions. While price and physicalenvironment have a negative influence on purchasing decisions, 3)Of the five marketing mix variables that have a positive effect onpurchasing decisions, product variables are the most dominantvariable in influencing purchasing decisions. 4) Product, price,promotion, place, person, physical environment and process havecontribution of 78.5% in explaining buying decision at food centerof Selorejo Reservoir. While other factors have a contribution of21.5% explained by other variables.